Nutritional advice in older patients at risk of malnutrition during treatment for chemotherapy: a two-year randomized controlled trial. - Isabelle Bourdel-Marchasson; Christelle Blanc-Bisson; Adélaïde Doussau; Christine Germain; Jean-Frédéric Blanc; Jérôme Dauba; Cyril Lahmar; Eric Terrebonne; Cédric Lecaille; Joël Ceccaldi; Laurent Cany; Sandrine Lavau-Denes; et al. (PLoS ONE, 2014)
We tested the effect of dietary advice dedicated to increase intake in older patients at risk for malnutrition during chemotherapy, versus usual care, on one-year mortality.We conducted a multicentre, open-label interventional, stratified (centre), parallel randomised controlled trial, with a 1∶1 ratio, with two-year follow-up. Patients were aged 70 years or older treated with chemotherapy for solid tumour and at risk of malnutrition (MNA, Mini Nutritional Assessment 17-23.5). Intervention consisted of diet counselling with the aim of achieving an energy intake of 30 kCal/kg body weight/d and 1.2 g protein/kg/d, by face-to-face discussion targeting the main nutritional symptoms, compared to usual care. Interviews were performed 6 times during the chemotherapy sessions for 3 to 6 months. The primary endpoint was 1-year mortality and secondary endpoints were 2-year mortality, toxicities and chemotherapy outcomes.Between April 2007 and March 2010 we randomised 341 patients and 336 were analysed: mean (standard deviation) age of 78.0 y (4·9), 51.2% male, mean MNA 20.2 (2.1). Distribution of cancer types was similar in the two groups; the most frequent were colon (22.4%), lymphoma (14.9%), lung (10.4%), and pancreas (17.0%). Both groups increased their dietary intake, but to a larger extent with intervention (p<0.01). At the second visit, the energy target was achieved in 57 (40.4%) patients and the protein target in 66 (46.8%) with the intervention compared respectively to 13 (13.5%) and 20 (20.8%) in the controls. Death occurred during the first year in 143 patients (42.56%), without difference according to the intervention (p = 0.79). No difference in nutritional status changes was found. Response to chemotherapy was also similar between the groups.Early dietary counselling was efficient in increasing intake but had no beneficial effect on mortality or secondary outcomes. Cancer cachexia antianabolism may explain this lack of effect.ClinicalTrials.gov NCT00459589.